2022
DOI: 10.3389/fpsyg.2022.812616
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Daily Mile™ on School Pupils’ Fitness, Cognition, and Wellbeing: Findings From Longer Term Participation

Abstract: BackgroundSchool based running programmes, such as The Daily Mile™, positively impact pupils’ physical health, however, there is limited evidence on psychological health. Additionally, current evidence is mostly limited to examining the acute impact. The present study examined the longer term impact of running programmes on pupil cognition, wellbeing, and fitness.MethodData from 6,908 school pupils (mean age 10.2 ± 0.7 years), who were participating in a citizen science project, was examined. Class teachers pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 51 publications
(74 reference statements)
1
27
0
Order By: Relevance
“…The improvements in executive function following the implementation of The Daily Mile in primary school children is a novel finding of the present study. However, this key finding is consistent with the limited previous research that has examined the effect of other school-based physical activity interventions on executive function in children 6 , 13 , yet is not in line with a large citizen science study that reported no differences in cognition between those young people who regularly complete The Daily Mile and those who do not 19 . Importantly, the present study is novel in that it specifically examined the effect of The Daily Mile using a randomised control design, rather than cross-sectionally comparing those who regularly do and do not complete The Daily Mile, as in previous work 19 ; where confounding variables could influence study outcomes.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The improvements in executive function following the implementation of The Daily Mile in primary school children is a novel finding of the present study. However, this key finding is consistent with the limited previous research that has examined the effect of other school-based physical activity interventions on executive function in children 6 , 13 , yet is not in line with a large citizen science study that reported no differences in cognition between those young people who regularly complete The Daily Mile and those who do not 19 . Importantly, the present study is novel in that it specifically examined the effect of The Daily Mile using a randomised control design, rather than cross-sectionally comparing those who regularly do and do not complete The Daily Mile, as in previous work 19 ; where confounding variables could influence study outcomes.…”
Section: Discussionsupporting
confidence: 79%
“…Tarp et al 14 also reported that a school-based physical activity intervention (specifically 20 weeks of classroom-based activities and active transport) had no effect on the attention of children aged 11–13 years, when attention was measured using the Flanker test. Whilst the findings of the present study, when taken in conjunction with those of Tarp et al 14 and the citizen science study of Booth et al 19 , suggest that school-based physical activity interventions have no effect on attention or working memory, research in the field to date is limited and there are many variables relating to school-based physical activity interventions that need to be explored in the future. Therefore, future research should examine the effect of different physical activity modes, durations, intensities, and frequencies to optimise school-based interventions for the enhancement of all domains of cognitive function in primary school children, with the aim to enhance as many cognitive domains as possible.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Fields included: author's names, year, study design, duration and sample characteristics. is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) [29] Quasi experimental between groups; Part of BBC Terrific Scientific project-data collected from schools on participation in TDM and categorised them as no participation, shorter term participation (2 months or less) and longer-term participation (3 months or more).…”
Section: Description Of Studiesmentioning
confidence: 99%